KEBIJAKAN STRUKTUR MODAL DAN EFEK WAKTU PASAR - Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
The capital structure policy of each entities often related with two main theories which are trade off and pecking order. But, there is another factor that could affecting the capital structure, which is market timing. The objective of this study is prove whether the capital structure of each entities are affected by these two main theories or market timing. Conducting regression analysis, this study found that, the capital structure of each entities in Indonesia most dominated by market timing, although as general, seems these entities following trade off model.